Entering the Global Arena Emerging States, Soft Power Strategies and Sports Mega-Events - Grix, Jonathan; Brannagan, Paul Michael; Lee, Donna; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Pivot, 2019)
Set against a backdrop of concerns about the potential break-up or radical change to the global world order, this volume sets out to investigate the use of sports mega-events by a number of emerging states. Sports mega-events, it is argued, can be understood as a key component in states' 'soft power' strategies, that is, their attempts to showcase their nations on the international stage, increase their power relative to others via non-coercive means and to increase trade and tourism. Many studies on soft power simply cite the concept's founder (Joseph Nye) and make little attempt at unpicking the mechanisms behind its creation. This volume does this by shining a light on emerging economies and by putting forward a soft power 'ideal type' to aid researchers in understanding the strategies employed by states in advancing their interests.
Chapter 1. Introduction -- Chapter 2. Emerging States and the Shifting Balance of Global Power -- Chapter 3. Sports Mega-Events and the Concept of Soft Power -- Chapter 4. Brazil's Double Host Status -- Chapter 5. Russia's Unique Soft Power Strategy -- Chapter 6. China's Coming Out Party? The Beijing Olympics, 2008 -- Chapter 7. South Africa and the 2010 FIFA World Cup finals -- Chapter 8. Qatar's Global Sports Strategy: Soft Power and the 2022 World Cup -- Chapter 9. Conclusion.
Keywords: Human geography; Political science; Sociology, Urban; Human Geography; Political Science; Urban Sociology